Tutorial: How to plot High-Quality Molecular Electrostatic Potential Surfaces (MEPS) ... - Mattia Felice, Palermo (ModelingHub, 2024)
ACCESS THE TUTORIAL HERE: https://modelinghub.xyz/tutorial-molecular-electrostatic-potential-surfaces-mep/ This tutorial on ModelingHub.xyz provides a comprehensive guide to generating and visualizing Molecular Electrostatic Potential Surfaces (MEPS) using ORCA and Chimera. It outlines the scientific importance of MEPS, details the required steps for running ORCA calculations, post-processing the data with a custom Python script, and accurately visualizing the results in Chimera. The guide emphasizes best practices for achieving reproducible, high-quality computational results, catering to the needs of computational chemists seeking detailed and objective-oriented methodologies. ...